Measuring visual perspective taking in the brain with avatars and arrows: Which question are we asking? - Schurz, M; Kronbichler, M; Weissengruber, S; Surtees, A; Perner, J (Elsevier, 2018)
There is an ongoing debate about the involvement of Theory of Mind (ToM) processes in Visual Perspective Taking (VPT). In an fMRI study (Schurz et al., 2015), we borrowed the positive features from a novel VPT task – which is widely used in behavioral research – to study previously overlooked experimental factors in neuroimaging studies. However, as Catmur et al. (2016) rightly argue in a comment on our work, our data do not speak strongly to questions discussed in the original behavioral studies, in particular the issue of implicit mentalizing. We appreciate the clarification of these interpretational limitations of our study, but would like to point out the differences between questions emerging from behavioral and neuroimaging research on VPT. Different from what Catmur et al. (2016) discuss, our study was not intended as a test of implicit mentalizing. In fact, the terms “automatic” and “implicit mentalizing” were never mentioned in our manuscript. Our study addressed a methodological gap between ToM and VPT research, which we identified in two previous meta-analyses on the topics (Schurz et al., 2013, 2014). With this difference in mind we show that the critical points levelled by Catmur et al. (2016) cease to apply.